Knowledge and Attitude Towards Assessment and Testing Among School and Other Practising Counsellors in Nigeria - Osumah, Obaze Agbonluae; Ehigbor, B. O.; Osemeikhian, Edowaye (Bisma The Journal of Counseling, 2024)
This study addressed the problem of limited knowledge and varying attitudes towards assessment and testing among school and practicing counsellors in Nigeria. The research aimed to explore the relationships between knowledge and attitudes towards these practices. Using four research questions and hypotheses, the study targeted all counsellors in Nigeria, with a purposive random sample of 350 participants drawn from attendees at the annual APROCON and CASSON conferences. Data were collected through the "Knowledge and Attitude towards Assessment and Testing among School and Practicing Counsellors in Nigeria Scale (KAATSOPCNS)," developed after an extensive literature review. Analysis was conducted using Pearson Product Moment Correlation Coefficient (PPMCC). The findings revealed significant relationships between counsellors' knowledge and attitudes towards assessment and testing, emphasizing the need for deeper understanding and professional competence. It is recommended that counsellors acquire requisite qualifications, gain practical experience, and participate in regular professional development programs to enhance their proficiency in assessment and testing. These steps are essential to ensure effective counselling practices in Nigeria.